Nurses and doctors 's awareness and knowledge towards treatment and care of cervical cancer patients: a cross-sectional study - Zhen Li; Sinuo Chen; Ishrat Mahjabeen; Rabia Shafique (BMC, 2023)
Abstract Aim The present study aimed to investigate healthcare professionals' perceptions and experiences in caring for cervical cancer patients. The present study was also designed to assess the healthcare professionals' attitudes toward cervical cancer screening and its prevention. Methods A cross-sectional quantitative descriptive study was conducted, and 540 participants (240 nurses and 300 doctors), from different hospitals of Pakistan have been selected and interviewed. Results Data was collected using structured questionnaires and SPSS was used to statistically analyze the data. Participants in the present study are questioned with respect to age, gender, and work experience. The mean age of the participants is 35 years. Among them, 41% of participants are < 35 years of age and 59% are > 35 years of age. In the case of gender, 22% of participants are males and 78% are females. 47% of the participants have work experience < 20 years and 53% have work experience > 20 years. Data from the present study showed that most of the nurses are less educated (basic education of middle and matric degree) with a simple diploma in nursing and midwifery. Nurses and doctors do not have any knowledge/experience of the patient's psychological counselling. Participants are also questioned with respect to HPV vaccination, 39% of nurses and 62% of doctors are vaccinated. The difference in vaccination frequency of participants was observed as statistically significant (p < 0.0001). In the case of treatment modalities, doctors have statistically more knowledge about the pap smear (p < 0.0001), cervical biopsy (p < 0.0001), colposcopy (p < 0.0001), and visual application after acetic acid application (p < 0.0001) compared to nurses. Data analysis showed that Pap smear was performed significantly higher in married females compared to unmarried (p < 0.0001). Conclusion our study provides a comprehensive and in-depth perspective of the nurses and doctors for cervical cancer patients. Cervical cancer prevalence is increasing due to inadequate knowledge and awareness among healthcare professionals. Improvement can be brought about by the regular use of treatment modalities in unmarried females also.